Using a two-level dynamic PDE model to synchronize the performance of technological equipment of a production line - Pihnastyi, O. M.; Ivanovska, O. V. (Національний університет "Одеська морська академія", 2021)
The problem of designing a system for optimal operational control of random deviations in the productivity of technological equipment is considered. To construct an algorithm for optimal control of the performance of technological equipment, a PDE-model of a production flow line was used. The Lyapunov functions method was used to determine the value of the optimal control of the technological equipment performance. The production line is considered by a distributed dynamic system. Equations are written for the flow parameters of the production line in small perturbations. A criterion for the quality control of the performance of technological equipment of a production flow line has been introduced. Based on this criterion, the Lyapunov function is determined for the considered production system. Taking into account the form of the Lyapunov function, control actions are obtained that correct the performance of the technological equipment. The introduced control made it possible to ensure the synchronization of the productivity of the technological equipment of the production line and the asymptotic stability of the given planned state of the flow parameters of the production line for the steady and transient operation mode.

Розглянуто завдання проектування системи оптимального оперативного контролю випадкових відхилень продуктивності технологічного обладнання. Для побудови алгоритму оптимального управління продуктивністю технологічного обладнання використовувалась PDE-модель виробничої потокової лінії. Для визначення значення оптимального управління продуктивністю технологічного обладнання використовувався метод функцій Ляпунова. Виробнича лінія розглядається розподіленою динамічною системою. Рівняння записані для параметрів потоку виробничої лінії при малих збуреннях. Введено критерій контролю якості роботи технологічного обладнання виробничої потокової лінії. На основі цього критерію визначається функція Ляпунова для розглянутої виробничої системи. З урахуванням форми функції Ляпунова отримані керуючі впливу, коригуючі роботу технологічного обладнання. Введене управління дозволило забезпечити синхронізацію продуктивності технологічного обладнання виробничої лінії і асимптотичну стійкість заданого планового стану параметрів потоку виробничої лінії для усталеного і перехідного режиму роботи.
Використання дворівневої динамічної моделі PDE для синхронізації продуктивності технологічного обладнання виробничої лінії
Keywords: production line; production control system; PDE-model; continuous production; synchronized production line; work in progress; distributed production system; виробнича лінія; система управління виробництвом; PDE-модель; безперервне виробництво; синхронізована виробнича лінія; незавершене виробництво; розподілена виробнича система